Potter Wasps of Florida, Eumenes spp. (Insecta: Hymenoptera: Vespidae: Eumeninae) - E. E. Grissell (EDIS)
EENY-403, a 3-page fact sheet by E. E. Grissell, is part of the Featured Creatures Collection. It describes this wasp which make the familiar jug-like nests found around the home, its distribution, identification, biology, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.